Utilization of cocoa pod husk and wood charcoal into briquettes as an environmentally friendly alternative fuel. - Arriza Novan Tahta Aunillah, Mohammad; Bayu Cezarridfalah, Bintang; Kirana Putri, Jesika; Nurmawati, Ardika; Ariefandie Febrianto, Noor; Adi Saputro, Erwan (Indonesian Coffee and Cocoa Research Institute, 2024)
Many efforts have been made to convert cocoa pod husk waste into charcoal briquettes, but they have not yet met the established Indonesian National Standard(SNI). Therefore, steps are needed to produce charcoal briquettes that comply with these standards. One approach that can be taken is by blending cocoa podhusk with wood charcoal since wood charcoal has a sufficiently high calorific value that can enhance the quality of the charcoal briquettes. This research aimsto find the optimal conditions for making briquettes from cocoa pod husk and identify the impact of briquette composition and carbonization time on valuessuch as moisture content, ash content, calorific value, and burning rate of the produced briquettes. The research process includes carbonization, grinding, sieving, adding a binder, and drying, followed by testing the briquettes’ characteristics. This research was conducted by comparing the mass composition of cocoa pod husk charcoal and wood charcoal at ratios of 100:0, 75:25, 50:50, and 25:75, with carbonization times of 1.5, 2, 2.5, and 3 hours. The best analysis results, in accordance with the Indonesian National Standard (SNI), were obtained at a carbonization time of 2 hours with a composition of 50:50 (cocoa pod husk:wood charcoal). The values include a moisture content of 5.944%, ash content of 7.83571%, calorific value of 4388.5 kcal kg -1 , and burning rate of 0.0034 g second -1 . The length of the carbonization process has a significant impact on the characteristics of the resulting briquettes, including moisture content, ash content, calorific value and burning rate. The longer the carbonization process, the lower the moisture content and ash content, and the higher the heating value and burning rate.